Antibody-Mediated Rejection: Pathogenesis, Prevention, Treatment, and Outcomes - Olivia R. Blume; Sarah E. Yost; Bruce Kaplan (Journal of Transplantation)
Antibody-mediated rejection (AMR) is a major cause of late kidney transplant failure. It is important to have an understanding of human-leukocyte antigen (HLA) typing including well-designed studies to determine anti-MHC-class-I-related chain A (MICA) and antibody rejection pathogenesis. This can allow for more specific diagnosis and treatment which may improve long-term graft function. HLA-specific antibody detection prior to transplantation allows one to help determine the risk for AMR while detection of DSA along with a biopsy confirms it. It is now appreciated that biopsy for AMR does not have to include diffuse C4d, but does require a closer look at peritubular capillary microvasculature. Although plasmapheresis (PP) is effective in removing alloantibodies (DSAs) from the circulation, rebound synthesis of alloantibodies can occur. Splenectomy is used in desensitization protocols for ABO incompatible transplants as well as being found to treat AMR refractory to conventional treatment. Also used are agents targeted for plasma cells, B cells, and the complement cascade which are bortezomib rituximab and eculizumab, respectively.